Distribution and Characteristics of Microplastics in Barnacles and Wild Bivalves on the Coast of the Yellow Sea, China - Zhang, Tao; Song, Kexin; Meng, Liting; Tang, Ruikai; Song, Tongtong; Huang, Wei; Feng, Zhihua (Frontiers in Marine Science, 2022)
Barnacles and bivalves are two well-known sessile invertebrates that play important roles in marine ecosystems. Microplastic (MP) pollution has attracted widespread attention. Barnacles and wild bivalves are smaller than farmed individuals; thus, they may be more sensitive to MPs. However, less is known about the abundance and spatial distribution of MPs in wild bivalves along with the coastal areas of China. This study evaluates MP pollution in the most abundant bivalves and barnacles (Crassostrea gigas, Ostrea cucullata, Mytilus edulis, and Balanus albicostatus) at five stations in the intertidal zone of the Yellow Sea. B. albicostatus was divided into ecotype A and ecotype B. The abundance of MPs in barnacles, wild bivalves barnacles, and wild bivalves varied from 0 to 2.25 items/individual and 0 to 118.21 items/g. O. cucullata and B. albicostatus (ecotype A) had the highest abundance of MPs, with average abundances of 0.56 ± 0.36 items/individual and 21.59 ± 27.26 items/g, respectively. The types of MPs found in bivalves and barnacles include fibers, fragments, films, and microbeads. The most abundant size was less than 1,000 μm, which accounted for 53% of the total MPs. Cellophane (CP), polypropylene (PP), polyethylene (PE), and polyethylene terephthalate (PET) were the main polymer types in bivalves and barnacles. This study suggests that the abundance of MPs in wild bivalves is close to that of farmed bivalves with commercial specifications, despite their smaller size. The MP abundance of barnacles in the Yellow Sea is higher than that in other areas in terms of items per gram. In addition, the ecological type may affect the ability of barnacles to accumulate MPs. Ingestion of MPs by barnacles and wild bivalves should be of concern because they may enter the human body through the food web and may pose a potential threat to human health.